An integrative system biology approach to delineate complex genotype-phenotype associations in Autism Spectrum Disorder - Asif, M. (2017)
Objectives: The global objective of the study is to improve the current knowledge on ASD prognosis and diagnosis by delineating the complex genotype-phenotype associations using an integrative systems biology approach. For this purpose three specific objectives were pursued: - To identify clinically similar subgroups of individuals with ASD; - To find biological processes disrupted by rare CNVs targeting brain genes in ASD subjects; - To train a machine learning classifier for the clinical prediction of disease progression from genetic information in very young children.